2018
DOI: 10.1177/0954407018790176
|View full text |Cite
|
Sign up to set email alerts
|

Combustion phasing modeling and control for compression ignition engines with high dilution and boost levels

Abstract: Because fuel efficiency is significantly impacted by the timing of combustion in internal combustion engines, accurate control of combustion phasing is critical. In this paper, a nonlinear combustion phasing model is introduced and calibrated, and both a feedforward model-based control strategy and an adaptive model-based control strategy are investigated for combustion phasing control. The combustion phasing model combines a knock integral model, burn duration model and a Wiebe function to predict the combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Where τ f is representing the fuel vapor process at some fixed amount of time indicated by ( s ), is representing the fuel flow injection [ kg / s ], the flow of fuel in the cylinders is given by the vapor fuel flow [ kg / s ], and the liquid mass fuel flow [ kg / s ], To produce a more comprehensive model, it is possible to add ϰ as a vector dependent on the throttle opening or engine r/min N e [ 37 ]. In our scenario, the second option is more practical.…”
Section: Methodsmentioning
confidence: 99%
“…Where τ f is representing the fuel vapor process at some fixed amount of time indicated by ( s ), is representing the fuel flow injection [ kg / s ], the flow of fuel in the cylinders is given by the vapor fuel flow [ kg / s ], and the liquid mass fuel flow [ kg / s ], To produce a more comprehensive model, it is possible to add ϰ as a vector dependent on the throttle opening or engine r/min N e [ 37 ]. In our scenario, the second option is more practical.…”
Section: Methodsmentioning
confidence: 99%
“…This TPA model can predict CA50 in the simulation with a ±0.84 CAD uncertainty as compared to experimental results [38]. Additional details regarding the agreement between the GT-ISE simulation model and experimental results can be found in [22] and [38]. Prior work has shown that the cylinderto-cylinder variations observed on this engine and are mainly caused by uneven mixing between the EGR, the quantity of fresh air, and any port-injected fuel.…”
Section: Ca50 Model Validation Diesel Engine Simulation Setupmentioning
confidence: 99%
“…CA50 is predicted using a SOC and BD model. These models are discussed in more detail in Sui and Hall 23 but are discussed briefly here for completion.…”
Section: Modeling Diesel Engine Combustion Phasingmentioning
confidence: 99%
See 2 more Smart Citations